Mass transfer of an implanted dopant in materials under high-power pulsed Ion beam impact; 7th International Conference on Modification of Materials with Particle Beams and Plasma Flows (Tomsk, Russia, 25-30 July 2004) - Petrov A. V.; Polkovnikova N. M; Ryabchikov A. I. Aleksandr Ilyich; Sokhoreva V. V.; Struts V. K.; Usov Y. P. Yuri Petrovich; Shulepov I. A. Ivan Anisimovich (2004, 2004)
The results of experimental studies of the mass transfer features in Ti-Si and Ti-Fe systems during repeated alternate processes of Ti ion implantation and irradiation with a high-power ion beam are presented for ion beam energy densities of ≤ 2 J/cm2. The analysis of the final state of samples surface after the combined treatment is carried out.